Exploring Artificial Intelligence's Role in Second Language Vocabulary Acquisition: Insights from Students' and Teachers' Perspectives - Faria Shaheen,; Khadija Gulam Hussain,; Dr.Mudasar Jahan,; Lubna Aram Azam, (Al-Qanṭara, 2024)
Artificial Intelligence (AI) is a need of the hour and has a strong relationship with classrooms and teaching styles. Different AI applications are in vogue nowadays to make lectures more comprehensive in academia. This study investigates how people in English Language Learning Classrooms use these applications of AI to teach and learn vocabulary in English as a Second Language (ESL) classrooms. The basic aim of the study is to know the opinion of students and teachers on how AI may be helpful in a pedagogical environment so far as vocabulary acquisition of English is concerned. This study also explores the pros and cons of AI in teaching and learning vocabulary through the opinions of students and teachers. The study is mixed-method in nature. The selected population for the study were 10 English language instructors and 100 University students, including 50 students of a class from Gift University Gujranwala and 50 from the University of Gujrat. That is, the research is comparative. For the quantitative portion; the Questionnaire was used as a source of data collection method. A questionnaire ‘Likert scale’ was prepared and filled out from the selected population. The range of questions was asked as benefits, comfort, advantages, effectiveness, trust in AI's recommendations, frequency of AI tool usage, replacement of human agent, Advantages of AI over the traditional method, Method of question asking, and replacement of a teacher were the ten factors related to AI and AI integration in vocabulary learning were the ten factors associated with AI integration in vocabulary learning that was validated through exploratory analysis. The responses are displayed through tables and figures. For qualitative data analysis, an exploratory-based open-ended questionnaire was prepared, and thematic analysis was performed. The results conclude that students, on the whole, are in favor of AI's contribution to vocabulary learning. They consider AI the more efficient and convenient to use application since it offers a close connection so far as learning vocabulary is concerned. The study focuses more on the fact that it is non-human, and students feel less social being the teacher is absent, that is, the absence of human engagement. Overall, students were in favour of AI being more available and easy to access than a teacher. Junior teachers also aligned with their opinion, while senior teachers were shown a worrying attitude and were not in favour of AI. Thus, students' attitudes were positive while teachers were negative. The results of this study may deepen our understanding of how artificial intelligence (AI) is seen in circumstances related to ESL/EFL vocabulary learning and how it may affect instructional strategies. Keywords: Artificial Intelligence (AI), Vocabulary, acquisition, E.S.L., Students-teacher, Second Language Acquisition.